Gomisin G hydrogel based on freeze-drying remodeling method and preparation method and application thereof

The lyophilized remodeling method for preparing Gomicin G nanoparticle hydrogels solved the problems of low water solubility and bioavailability of Gomicin G, achieving intestinal targeted delivery and significantly improving cognitive function impairment and intestinal inflammation in aluminum-induced AD mice, demonstrating significant therapeutic effects.

CN123038010APending Publication Date: 2026-11-06EASTERN LIAONING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611450319.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-17
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Gomicin G has poor water solubility and low local bioavailability, making it difficult to achieve effective enrichment and long-lasting effects in intestinal inflammatory lesions. Existing technologies make it difficult to develop drug formulations that can improve its water solubility and enhance its bioavailability.

Method used

Gomicin G nanoparticle hydrogels were prepared by freeze-drying remodeling. By selecting Gomicin G nanoparticles with a particle size of 100-120 nm, combining DSPE-MPEG2000 as a solubilizer, chitosan and sodium carboxymethyl cellulose as polymer materials, calcium chloride as a coagulant, and sucrose as a freeze-drying protectant, a stable nanoparticle hydrogel was formed to achieve intestinal targeted delivery.

Benefits of technology

Gomisin G hydrogel achieves targeted delivery to intestinal inflammatory areas, increasing local drug concentration and duration of action, effectively inhibiting intestinal inflammatory response, repairing damaged intestinal barrier structure, blocking the transmission of intestinal pro-inflammatory signals to the central nervous system, and reversing aluminum-induced cognitive impairment in AD mice.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123038010A_ABST
    Figure CN123038010A_ABST
Patent Text Reader

Abstract

This invention provides a gomisin G hydrogel based on a freeze-drying remodeling method, its preparation method, and its application, belonging to the field of pharmaceutical formulation technology. The gomisin G hydrogel comprises gomisin G, a solubilizer, a polymeric material, a coagulant, and a freeze-drying protectant. The preparation method is as follows: gomisin G and the solubilizer are mixed and dissolved in anhydrous ethanol to obtain an organic phase; this organic phase is then mixed with an aqueous phase to obtain a gomisin G solution; a coagulant is added to the polymeric material to obtain a blank hydrogel; the blank hydrogel is then washed with a freeze-drying protectant, freeze-dried, and reconstituted with the gomisin G solution to obtain the gomisin G hydrogel. The drinkable gomisin G hydrogel prepared by this invention significantly improves learning and memory, motor coordination, and anxiety-like behavior in mice, and significantly inhibits abnormal deposition of β-amyloid protein and Tau protein in the right hemisphere. This invention not only provides an intervention strategy for aluminum-induced AD but also provides a theoretical basis for the development of a drug delivery system for the active ingredient of Schisandra chinensis lignans.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of pharmaceutical formulation technology, and particularly relates to a gomisin G nanoparticle hydrogel based on freeze-drying remodeling method, its preparation method and application. Background Technology

[0002] Alzheimer's disease ( Alzheimer's disease Alzheimer's disease (AD) is a common neurodegenerative disease in clinical practice, and its typical pathological feature is the presence of β-amyloid plaques in the brain. Beta-amyloid Abnormal deposition of Aβ and Tau proteins and persistent neuroinflammatory infiltration are observed. Related studies have confirmed that gut-brain axis dysfunction plays a key mediating role in the progression of Alzheimer's disease (AD). Imbalance in intestinal mucosal homeostasis and increased intestinal barrier permeability due to chronic inflammation promote the intrusion of harmful substances such as inflammatory factors and endotoxins into the peripheral bloodstream. These substances, transported through the bloodstream, activate inflammatory cascade pathways in the right hemisphere, further increasing the abnormal aggregation of Aβ and Tau proteins, forming a pathological cascade reaction loop of "intestinal inflammation - intestinal barrier damage - peripheral inflammation activation - central nervous system degenerative changes." Currently, animal models constructed using aluminum chloride gavage can effectively simulate the pathological features of aluminum exposure-mediated intestinal barrier damage and intestinal inflammation.

[0003] Gomicin G is a lignan-based natural active ingredient extracted from Schisandra chinensis. Existing studies have confirmed its significant anti-inflammatory, antioxidant, and neuroprotective pharmacological activities. This component can effectively inhibit the release of pro-inflammatory factors in the intestine, repair damaged intestinal mucosal tissue structure, and alleviate chronic intestinal inflammation. It can also block the transmission of enterogenic inflammatory signals to the central nervous system, reducing the degree of neuroinflammatory infiltration in the brain. However, Gomicin G suffers from poor water solubility and low local bioavailability, making it difficult to achieve effective accumulation and long-lasting effects at the lesions of intestinal inflammation.

[0004] Therefore, developing a drug formulation that can improve the water solubility of Gomecin G, enhance its bioavailability in vivo, increase the local drug concentration at the lesion site, prolong the duration of drug action, and achieve the therapeutic effects of regulating intestinal inflammation, repairing the intestinal barrier, and intervening in the gut-brain axis disorder is a technical challenge that urgently needs to be solved in this field. Summary of the Invention

[0005] To address the aforementioned problems in the prior art, this invention provides a gomisin G nanoparticle hydrogel based on a freeze-drying remodeling method, its preparation method, and its applications. The gomisin G hydrogel prepared by this invention is drinkable and, after oral administration to the intestinal tract, can effectively inhibit intestinal inflammatory responses, repair damaged intestinal barrier structures, block the transmission of intestinal pro-inflammatory signals to the central nervous system, thereby reversing aluminum-induced cognitive impairment in AD mice.

[0006] To achieve the above objectives, the present invention provides the following technical solution: One of the technical solutions of the present invention: This invention provides a gomisin G hydrogel based on a freeze-drying remodeling method, wherein the gomisin G hydrogel comprises gomisin G, a solubilizer, a polymer material, a coagulant, and a freeze-drying protectant.

[0007] Furthermore, the mass ratio of the gomisin G, solubilizer, polymer material, coagulant and freeze-drying protectant is 1:(5-100):(100-1000):(1-10):(10-100).

[0008] Furthermore, the particle size of the gomisin G is 100-120 nm; Beneficial effects: This invention selects gomisin G with a particle size of 100-120 nm because gomisin G in this particle size range has the following significant advantages: (1) Suitable balance between intestinal mucosal adhesion and penetration: The nanoparticle size is in the range of 100-120 nm. It can enhance the hydrogen bond / electrostatic interaction with the intestinal mucosal mucus layer by utilizing its high specific surface area, thereby achieving good bioadhesion and retention effect and prolonging the residence time of the drug in the intestinal inflammatory lesion. At the same time, this size is not enough to penetrate tight junctions (~10~20 nm) or be efficiently transported by M cells, which can avoid the risk of systemic exposure caused by a large amount of nanoparticles entering the blood, and ensure that the drug mainly exerts its therapeutic effect locally in the intestinal wall. (2) Avoid being rapidly cleared by macrophages: Nanoparticles with a diameter greater than 100 nm are not easily phagocytosed and cleared by macrophages in the intestinal lamina propria (macrophages have significantly increased internalization efficiency for particles <100 nm), which helps maintain the local effective drug concentration; (3) Suitable solubilizing loading efficiency: The hydrophobic core size of DSPE-MPEG2000 micelles is about 10-20 nm. When the particle size of Gomicin G is controlled at 100-120 nm, a single nanoparticle is assembled from multiple solubilizing micelles. The ratio of drug to solubilizer is moderate, which can achieve sufficient loading without causing intestinal irritation due to excessive solubilizer usage. If the particle size of Gomecin G is less than 100 nm (e.g., <100 nm), the following adverse effects will occur: 1) The specific surface area of ​​the nanoparticles increases dramatically, the surface free energy increases, and the particles are prone to aggregation and fusion, resulting in a significant decrease in the stability of the formulation; 2) The small particle size makes it easier for the nanoparticles to diffuse rapidly through the intestinal mucus layer and be efficiently phagocytosed and transported into the blood by M cells, resulting in a shorter local retention time of the drug at the inflammatory lesion and an increased safety risk of non-specific exposure throughout the body; 3) When the particle size is too small, the multivalent binding of nanoparticles to receptors on the surface of intestinal epithelial cells is weakened, and the cell uptake efficiency decreases, which is not conducive to the effective accumulation of the drug in the intestinal wall tissue; 4) A higher proportion of solubilizer needs to be added during the preparation process to maintain the colloidal stability of the small particle size, and the increased amount of excipients may bring additional risks of intestinal irritation.

[0009] Therefore, the present invention preferably controls the particle size of Gomecin G within the range of 100-120 nm, which ensures the physical stability of the formulation and its local retention capacity in the intestine, while avoiding the risk of systemic exposure and formulation instability caused by excessively small particle size. This is the ideal particle size window for the hydrogel to achieve safe and efficient intestinal targeted delivery.

[0010] Further, the solubilizer includes one or more of polyethylene glycol derivatives, polysialic acid derivatives, polylactic acid derivatives and phospholipids, preferably polyethylene glycol derivatives, more preferably 1,2-distearate-sn-glycerol-3-phosphatidylethanolamine-polyethylene glycol 2000 (DSPE-MPEG2000).

[0011] Beneficial effects: The present invention prefers DSPE-MPEG2000 as a solubilizer because: (1) Unique amphiphilic molecular structure enables efficient drug encapsulation DSPE-MPEG2000 is an amphiphilic copolymer composed of distearate phosphatidylethanolamine (DSPE) and methoxy-terminated polyethylene glycol 2000 (mPEG2000) linked by amide bonds. Its molecule consists of a hydrophobic tail (providing lipophilicity, allowing embedding in lipid bilayers or nanoparticle cores) formed by two stearic acid chains and a hydrophilic PEG head. This structure enables it to spontaneously assemble into nanomicelles or lipid nanoparticles in an aqueous environment: the hydrophobic DSPE core efficiently encapsulates poorly soluble gomisin G, while the PEG shell significantly improves the water solubility and dispersion stability of the drug-loaded system. Other solubilizers (such as common phospholipids, polysialic acid derivatives, or polylactic acid derivatives) often possess only single hydrophilic or hydrophobic properties, making it difficult to simultaneously achieve both efficient encapsulation and good water solubility.

[0012] (2) Excellent colloidal stability and process compatibility DSPE-MPEG2000 combines the amphiphilic properties of phospholipids with the hydrophilic polymer properties of PEG, exhibiting a solubility of approximately 3-4 g / 100 mL in water and good solubility in lower alcohols (such as ethanol). This solubility characteristic makes it perfectly suited for the "anhydrous ethanol dissolution-aqueous precipitation" nanoparticle preparation process of this invention: DSPE-MPEG2000 is thoroughly mixed and dissolved with Gmisin G in the organic phase, and upon transfer to the aqueous phase, it immediately self-assembles to form a stable nanomicelle structure, effectively buffering the risk of drug precipitation caused by sudden changes in solvent polarity and ensuring uniform nanoparticle size (approximately 120 nm). Simultaneously, the nanosystem constructed with DSPE-MPEG2000 exhibits excellent long-term storage stability and reconstitution stability, making it suitable for industrial production and application.

[0013] (3) Advantages compared with other solubilizers Compared to ordinary phospholipids: Although ordinary phospholipids (such as egg yolk lecithin and soybean phospholipids) have certain solubilizing abilities, they lack PEGylation modification. The nanocarriers constructed from them have short in vivo circulation time, poor stability, and are easily cleared by the MPS system. DSPE-MPEG2000, on the other hand, achieves a dual upgrade of "long circulation" and "stealth" through PEG segments.

[0014] Compared to polysialic acid derivatives: While polysialic acid (PSA) possesses good biocompatibility and non-immunogenicity, its main advantage lies in the modification and delivery of large molecule drugs (such as proteins and peptides). Its solubilization efficiency and loading capacity for small molecule lignan drugs are limited, and its synthesis process is complex and costly. Compared to polylactic acid derivatives: Although polylactic acid (PLA) and its copolymers (PLGA) are biodegradable, their degradation products (lactic acid, glycolic acid) are acidic, and long-term in vivo application may induce local inflammatory reactions. Furthermore, PLA-based materials have extremely low water solubility, making them difficult to directly apply to the "organic phase-aqueous phase" nanoprecipitation process described in this invention; additional surfactants or complex emulsification processes are required to achieve nano-scale formation. DSPE-MPEG2000, on the other hand, combines good water and ethanol solubility, offering superior process adaptability.

[0015] In summary, the preferred solubilizer of this invention is DSPE-MPEG2000, which is a comprehensive choice based on its unique amphiphilic molecular structure, long-cycle PEGylation characteristics, excellent process adaptability, and significant suitability for the application scenarios of this invention. The technical effects it achieves are difficult to replace by other conventional solubilizers (such as ordinary phospholipids, polysialic acid derivatives, polylactic acid derivatives, etc.).

[0016] Furthermore, the polymeric material includes one or more of chitosan, polyhyaluronic acid, sodium carboxymethyl cellulose, and polysialic acid, preferably a mixture of chitosan and sodium carboxymethyl cellulose, with a mass ratio of chitosan to sodium carboxymethyl cellulose of 1:4.

[0017] Furthermore, the coagulant includes one or more of calcium chloride, zinc chloride, aluminum chloride, and magnesium chloride, preferably calcium chloride.

[0018] Beneficial effects: This invention preferentially uses calcium chloride as a coagulant, which has the following significant advantages compared to other coagulants (zinc chloride, aluminum chloride, magnesium chloride): (1) Calcium ion-mediated “double cross-linking” mechanism to construct a stable hydrogel network Calcium chloride dissociates into Ca when dissolved in water. 2+ and Cl - Ca 2+ It plays a dual crosslinking role in the CS / CMC-Na composite system of this invention: First stage (electrostatic cross-linking reinforcement): Ca 2+ As a positively charged divalent cation, it can bridge two adjacent carboxylate ions (-COO) on the CMC-Na molecular chain. - This forms an "eggshell structure" coordination complex, significantly enhancing the cross-linking density between CMC-Na molecular chains. Simultaneously, Ca... 2+ It can coordinate with the partially deprotonated amino groups on the chitosan molecular chain, further strengthening the polyelectrolyte complex network structure between CS-CMC-Na, thus significantly improving the mechanical strength of the hydrogel.

[0019] Second stage (promoting in-situ gelation): Ca 2+ When mixed with polymer materials, the crosslinking rate can be controlled by ion diffusion. In the system of this invention, Ca... 2+ The cross-linking mechanism involves gradual diffusion from the surface of the polymer material inwards, forming a gradient cross-linked structure from the outside in, resulting in a uniformly formed, smooth, and dense hydrogel. This dual cross-linking mechanism endows the blank hydrogel with excellent formability and structural stability, allowing it to maintain a good porous network structure even after freeze-drying, and its mechanical properties to recover rapidly after reconstitution.

[0020] (2) Precisely control the gelation rate to match the preparation process window Calcium chloride has extremely high solubility in water (approximately 74.5 g / 100 g water at 20°C), and can completely dissociate in a very short time to provide sufficient Ca. 2+ By adjusting the amount of calcium chloride added (the preferred mass ratio of gomisin G to calcium chloride in this invention is 1:(1~10)), the crosslinking reaction rate and gelation time can be precisely controlled, avoiding uneven gel formation (excessive local crosslinking and high brittleness) caused by excessively rapid crosslinking or insufficient gel strength caused by excessively slow crosslinking. This control window is wide and has good process tolerance, making it suitable for the large-scale preparation process of this invention.

[0021] (3) Calcium ions are physiologically essential elements and have excellent safety. Calcium is one of the most abundant mineral elements in the human body, participating in many key physiological processes such as bone formation, nerve conduction, and muscle contraction. When calcium chloride is used as a coagulant, the uncoordinated free calcium molecules after cross-linking... 2+ It can be directly absorbed and utilized by the intestines without the risk of accumulation and toxicity.

[0022] (4) Advantages compared with other coagulants

[0023] (5) Synergistic compatibility with polymer materials Ca 2+ The ionic radius of Zn is 100 pm, which closely matches the spatial distance between two adjacent carboxyl groups on the CMC-Na molecular chain, enabling the formation of a stable six-membered ring "eggshell structure" complex. This coordination configuration is characteristic of Zn. 2+ (60 pm, too small) and Mg 2+ (72 pm, too small) is difficult to achieve. 3+ Although (54 pm) is a trivalent ion with strong cross-linking ability, its strong hydrolytic tendency (acidity) and neurotoxicity risk make it unsuitable for the AD treatment scenario of this invention. Therefore, calcium chloride is the optimal coagulant choice in terms of cross-linking efficiency, safety, and compatibility with the natural product drug delivery system of this invention.

[0024] Furthermore, the freeze-drying protectant includes one or more of sucrose, maltose, glucose, and lactose, preferably sucrose.

[0025] Beneficial effects: This invention preferentially uses sucrose as a freeze-drying protectant, which has the following significant advantages compared to other freeze-drying protectants (maltose, glucose, lactose): (1) Excellent "water substitution" effect, effectively protecting the three-dimensional network structure of hydrogel. During freeze-drying, the formation and growth of ice crystals cause irreversible mechanical damage to the three-dimensional network structure of the hydrogel, leading to a significant decrease in the mechanical properties of the hydrogel after reconstitution, or even complete loss of its moldability. Sucrose molecules are rich in hydroxyl groups, which can bond with polar groups (-NH2, -OH, -COO) on the polymer chains (chitosan, sodium carboxymethyl cellulose) in the hydrogel network via hydrogen bonds. - Extensive intermolecular hydrogen bonding occurs. During the freeze-drying process, sucrose molecules gradually replace water molecules and bind to the polymer chains, playing a protective role of "water substitution" or "water replacement." This effectively maintains the natural conformation and intermolecular spacing of the polymer chains in the dehydrated state, preventing irreversible aggregation or structural collapse of the polymer chains due to excessive dehydration. This ensures that the hydrogel network structure maintains a high degree of consistency before and after freeze-drying and rehydration.

[0026] (2) High glass transition temperature (T) g '), ensuring the structural integrity of the freeze-drying process Sucrose has a high glass transition temperature (T0) in its concentrated state. g ≈ -32℃, much higher than the T of glucose. g '≈-43℃ and T of maltose g At approximately -29.5℃, a high-viscosity glassy matrix can be rapidly formed during freeze-drying. This glassy state has the following dual protective functions: First, it restricts molecular motion; the high-viscosity glassy state can effectively restrict the movement and rearrangement of polymer chain segments, preventing structural relaxation and pore wall collapse of the hydrogel network during freeze-drying. Second, it inhibits ice crystal recrystallization; during storage after freeze-drying, the glassy matrix can effectively inhibit ice crystal recrystallization induced by residual moisture and Ostwald ripening, ensuring the long-term storage stability of the freeze-dried product. For the blank hydrogel prepared in this invention, high T... g The properties ensure that the porous framework formed after freeze-drying has a microstructure with uniform pore size and good connectivity, laying the structural foundation for the capillary penetration and uniform distribution of the subsequent Gomicin G solution.

[0027] (3) It has the dual functions of freeze-drying protection and reconstitution promotion. In addition to its lyophilization protective effect, sucrose in freeze-dried products also promotes penetration during reconstitution. Sucrose's high water solubility (approximately 200 g / 100 g water at 20°C) allows it to dissolve rapidly during reconstitution, creating a localized high-osmotic-pressure microenvironment within the freeze-dried matrix. This accelerates capillary wetting and penetration efficiency of water molecules, enabling the gomisin G solution to quickly and uniformly penetrate the hydrogel matrix, achieving rapid reconstitution and uniform drug redistribution. This dual effect is crucial for the clinical application of this invention. In clinical use, doctors or patients can obtain a homogeneous, accurately-content, drinkable gel formulation in a short time with simple reconstitution, significantly improving ease of use.

[0028] (4) Advantages compared with other lyophilization protectants

[0029] In summary, the preferred sucrose as a freeze-drying protectant in this invention is based on its comprehensive advantages in terms of water substitution protection, high glass transition temperature, non-reducing chemical stability, good reconstitution promotion, cost accessibility, and medication compliance. Its compatibility with the hydrogel matrix of this invention is significantly better than that of other commonly used freeze-drying protectants such as glucose, maltose, and lactose.

[0030] The second technical solution of the present invention: The present invention also provides a method for preparing the gomisin G hydrogel based on the freeze-drying remodeling method, comprising the following steps: (1) Gomexin G and solubilizer are mixed and dissolved in anhydrous ethanol to obtain an organic phase. The organic phase is then mixed with an aqueous phase to obtain a Gomexin G solution. (2) Add a coagulant to the polymer material, and obtain a blank hydrogel after cross-linking reaction. Then add a freeze-drying protectant to wash the blank hydrogel, then freeze-dry it, and finally add the gomisin G solution to re-dissolve it to obtain the gomisin G hydrogel.

[0031] Beneficial effects: In step (1), after mixing Gomecin G with a solubilizer, anhydrous ethanol is used to dissolve and prepare the organic phase. Anhydrous ethanol can fully disperse Gomecin G and break up the nanoparticle aggregates. During the mixing of the organic phase and the aqueous phase, ethanol rapidly diffuses into the aqueous phase, causing an increase in solvent polarity and a decrease in the solubility of Gomecin G. The solubilizer in the system interacts with Gomecin G through its amphiphilic structure, buffering the drug precipitation tendency caused by the sudden change in solvent, promoting the formation of a nanoscale dispersion structure of the drug, and obtaining a stable Gomecin G solution.

[0032] Further, the mixing ratio of gomisin G and anhydrous ethanol in step (1) is 1 mg: (10-100) mL; The volume ratio of the organic phase to the aqueous phase is 1:(10-20).

[0033] Furthermore, the washing in step (2) is performed using a 10% sucrose solution to wash away excess coagulant.

[0034] Furthermore, the freeze-drying process in step (2) is carried out at a temperature of -40°C for 24 hours.

[0035] The third technical solution of the present invention: The present invention also provides the application of the gomisin G hydrogel based on the freeze-drying remodeling method in the preparation of a drug for treating Alzheimer's disease.

[0036] The beneficial effects of this invention compared to the prior art are as follows: The Gomecin G hydrogel of the present invention has both good biocompatibility and intestinal mucosal adhesion properties, which can achieve targeted delivery of Gomecin G to the intestinal inflammatory area, increase the local drug concentration and duration of action at the lesion, and maximize its therapeutic effects in regulating intestinal inflammation, repairing the intestinal barrier and intervening in intestinal-brain axis disorders.

[0037] Long-term oral administration of aluminum chloride can directly disrupt the integrity of the intestinal epithelial barrier, inducing chronic intestinal inflammation. This, in turn, promotes the entry of peripheral pro-inflammatory mediators into the bloodstream, activating neutrophils, inducing central nervous system inflammation, and ultimately leading to cognitive impairment. The gomisin G hydrogel of this invention, after oral administration to the intestines, can effectively inhibit intestinal inflammatory responses, repair damaged intestinal barrier structures, and block the transmission of intestinal-derived pro-inflammatory signals to the central nervous system, thereby reversing cognitive impairment in aluminum-induced AD mice. The drinkable gomisin G hydrogel of this invention can significantly improve learning and memory, motor coordination, and anxiety-like behavior in mice, and significantly inhibit abnormal deposition of β-amyloid and Tau proteins in the right hemisphere. Its overall intervention effect is superior to that of the positive control drug donepezil hydrochloride. This invention not only provides an intervention strategy for aluminum-induced AD but also provides a theoretical basis for the development of a drug delivery system for the active ingredient of Schisandra chinensis lignans. Attached Figure Description

[0038] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0039] Figure 1 This is a schematic diagram illustrating the preparation process and application flow of the Gomicin G hydrogel in this invention; Figure 2 This is a visual comparison of physiological saline, blank hydrogel, gomisin G hydrogel and donepezil hydrochloride in Example 3 of the present invention. The upper image shows the static state and the lower image shows the tilted state. Figure 3 Figure 3 shows the body weight change curves of mice during modeling and drug treatment in Example 3 of the present invention. Figure a shows the body weight change curve of mice within 42 days of modeling, and Figure b shows the body weight change curve of mice within 28 days of treatment. Figure 4 The results of the mouse behavioral experiment during the treatment period in Example 4 of the present invention are shown in Figure a, which is the result of the time when each group of mice reached the bottom of the pole in the pole climbing experiment; Figure b is the result of the time when each group of mice stayed in the central area in the mine experiment; Figure c is the result of the number of times each group of mice entered the new arm in the Y maze experiment; and Figure d is the result of the escape latency of each group of mice in the water maze experiment. Figure 5Figure 5 shows the expression levels of Aβ and Tau proteins in the right hemisphere of mice in Example 5 of this invention. Figure a shows the Western Blot results of Aβ and Tau protein expression in the hippocampus of each group of mice, Figure b shows the quantitative analysis of the relative expression level of Aβ protein (Aβ / β-Actin) in each group of mice, and Figure c shows the quantitative analysis of the relative expression level of Tau protein (Tau / β-Actin) in each group of mice. Figure 6 The images shown are immunofluorescence staining images of the right hemisphere of mice in Example 6 of the present invention. Figure a shows representative immunofluorescence staining images of Aβ and Tau proteins in the right hemisphere of mice in each group. Figure b shows quantitative analysis of Aβ fluorescence intensity in the right brain section of mice in each group. Figure c shows quantitative analysis of Tau fluorescence intensity in the right brain section of mice in each group. Figure 7 The images show immunofluorescence staining of mouse small intestine in Example 7 of the present invention. Figure a shows representative immunofluorescence staining images of CXCR2 and Ly-6G proteins in the small intestine tissue of each group of mice. Figure b shows the quantitative analysis of CXCR2 fluorescence intensity in the cross section of the small intestine of each group of mice. Figure c shows the quantitative analysis of Ly-6G fluorescence intensity in the cross section of the small intestine of each group of mice. Figure 8 This is an in vitro cumulative release curve of the Gomicin G hydrogel during the release performance test in Example 8 of the present invention. Detailed Implementation

[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0041] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0042] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0043] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0044] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0045] The entire preparation process and application flow of the Gomisin G hydrogel of the present invention are as follows: Figure 1 As shown.

[0046] Example 1 A method for preparing gomisin G hydrogel based on freeze-drying remodeling includes the following steps: (1) Preparation of Gomicin G solution using microfluidic technology: Gomicin G (purity ≥98%) and DSPE-MPEG2000 were mixed and anhydrous ethanol was added. The mixture was stirred and dissolved at 60°C to obtain an organic phase. The organic phase was then mixed with the aqueous phase to obtain Gomicin G solution. The mass ratio of Gomicin G to DSPE-MPEG2000 was 1:20, the mixing ratio of Gomicin G to anhydrous ethanol was 1 mg:100 mL, and the volume ratio of the organic phase to the aqueous phase was 1:20.

[0047] (2) Using chitosan-carboxymethyl cellulose sodium (volume ratio of 1:4) as the matrix, calcium chloride was added to carry out cross-linking reaction to obtain blank hydrogel. Then, the blank hydrogel was washed with a 10% sucrose solution and then freeze-dried at -40℃ for 24 h. Finally, the above-mentioned gomisin G solution was added to reconstitute the hydrogel to obtain gomisin G hydrogel. The mass ratio of gomisin G, chitosan-carboxymethyl cellulose sodium, calcium chloride and sucrose was 1:200:1:10.

[0048] Example 2 (1) Preparation of Gomicin G solution using microfluidic technology: Gomicin G (purity ≥98%) and phospholipids were mixed and anhydrous ethanol was added. The mixture was stirred and dissolved at 60°C to obtain an organic phase. The organic phase was then mixed with the aqueous phase to obtain a Gomicin G solution. The mass ratio of Gomicin G to phospholipids was 1:20, the mixing ratio of Gomicin G to anhydrous ethanol was 1 mg:100 mL, and the volume ratio of the organic phase to the aqueous phase was 1:20.

[0049] (2) Using polyhyaluronic acid as a matrix, zinc chloride was added to carry out a cross-linking reaction to obtain a blank hydrogel. Then, the blank hydrogel was washed with a 10% glucose solution and then freeze-dried at -40℃ for 24h. Finally, the above-mentioned Gomicin G solution was added to re-dissolve the hydrogel to obtain Gomicin G hydrogel. The mass ratio of Gomicin G, polyhyaluronic acid as matrix, zinc chloride and glucose was 1:200:1:10.

[0050] Example 3: Establishment of an aluminum-induced Alzheimer's disease mouse model 1. Laboratory animals SPF-grade male C57BL / 6J black mice (to avoid interference from estrogen fluctuations), 8 weeks old, weighing 20-25 g, were housed in an environment with a temperature of 22±2℃, humidity of 50±10%, and a 12-hour light-dark cycle, with free access to food and water. Experiments began after one week of acclimatization. This experimental procedure was reviewed and approved by the Laboratory Animal Ethics Committee and complied with laboratory animal welfare and ethical guidelines throughout.

[0051] 2. Model Establishment After the adaptive feeding period, the mice were randomly divided into a control group and a model group. The model group mice were given a 2% AlCl3 solution by gavage at a dose of 100 mg / kg for 42 consecutive days. The control group mice were given an equal volume of physiological saline by gavage daily. The mice were weighed and recorded weekly to ensure a uniform dosage per unit body weight.

[0052] 3. Animal grouping After successful modeling, the model mice were randomly divided into 4 groups, plus a normal control group, for a total of 5 groups, with 8 mice in each group: A: Normal saline group (normal mice, treated with saline); B: Model control group (model mice, treated with saline). C: Positive control group (model mice, treated with donepezil hydrochloride); D: Model drug-loaded liposome group (model mice, blank hydrogel prepared in Example 1 for intervention); E: Model test preparation group (model mice, intervention with Gomexin G hydrogel prepared in Example 1).

[0053] The visual comparison diagrams of physiological saline, blank hydrogel, gomisin G hydrogel, and donepezil hydrochloride are shown below. Figure 2 As shown, through Figure 2 It can be seen that the Gomisin G hydrogel does not flow and maintains its shape when tilted, proving that it has good moldability and stability.

[0054] 4. Dosing regimen All groups started administration on the day following the end of model validation (day 43), via gavage, once daily for 28 consecutive days, at a dose of 5 mg / kg.

[0055] During the modeling and drug treatment period, the mice in each group were in good mental condition and had normal activity. The changes in body weight are shown in the graph below. Figure 3 As shown, by Figure 3 It can be seen that during the modeling and treatment periods, the body weight increased steadily and there was no significant difference between the groups, suggesting that Gomicin G hydrogel has no obvious systemic toxicity.

[0056] Example 4: Behavioral effects in mice during treatment 1. Pole Climbing Experiment (1) Experimental methods On day 30 of drug administration, a bar experiment was conducted. Mice were placed on the top of a horizontal bar, and the time it took for them to fall, stay, or climb down was recorded, with an upper limit of 300 seconds.

[0057] (2) Experimental results The results of the pole climbing experiment are as follows Figure 4 As shown in a, through Figure 4 As shown in Figure a, the time to reach the bottom of the rod in the normal group was 27.50 ± 8.19 s. The time to reach the bottom of the rod in the aluminum-induced AD model group was significantly prolonged to 248.83 ± 4.88 s (P<0.01 vs. normal group), indicating that the motor coordination ability of aluminum-induced AD mice was significantly impaired. The time to reach the bottom of the rod in the positive control group (donepezil hydrochloride) was 103.22 ± 6.31 s, significantly shorter than that in the model group (P<0.05 vs. model group). The time to reach the bottom of the rod in the blank hydrogel group was 249.83 ± 4.88 s, with no significant difference compared to the model group (P>0.05). The time to reach the bottom of the rod in the Gomisin G hydrogel group was significantly shortened to 74.50 ± 5.09 s (P<0.01 vs model group; P<0.01 vs normal group; P<0.05 vs positive drug group), which was still significantly different from the normal group. This indicates that Gomisin G hydrogel can significantly improve the motor coordination ability of aluminum-induced AD mice, but it cannot completely restore it to the normal level.

[0058] The above results indicate that gomisin G hydrogel can significantly improve motor coordination in aluminum-induced AD mice, and its efficacy is superior to that of donepezil hydrochloride, a positive control drug.

[0059] 2. Mine Field Experiment (1) Experimental methods The experiment was conducted on day 31 of drug administration. Mice were placed in the central area of ​​a mining test chamber (50 cm × 50 cm × 30 cm, matte black acrylic material), and a top camera recorded the total distance the mice moved and the time spent in the central area over 5 minutes. Anxiety-like behaviors were evaluated by the time the mice spent in the central area (25 cm × 25 cm).

[0060] (2) Experimental results: The results of the mine experiment are as follows Figure 4 As shown in b, through Figure 4 As shown in b, the time spent in the central region by normal mice was 51.83 ± 15.61 s. The time spent in the central region by aluminum-induced AD model mice was significantly increased to 181.17 ± 18.66 s (P < 0.01 vs. normal group), indicating that aluminum-induced AD mice exhibited significant anxiety-like behavior, specifically an increased tendency to avoid the central open region. The time spent in the central region by the positive drug control group (donepezil hydrochloride) was 105.67 ± 28.57 s, significantly lower than that of the model group (P < 0.05 vs. model group). The time spent in the central region by the blank hydrogel group was 176.00 ± 19.87 s, with no significant difference compared to the model group (P > 0.05). The residence time in the central region of the Gomexin G hydrogel group was significantly reduced to 101.50 ± 24.66 s (P<0.01 vs model group; P>0.05 vs normal group; P>0.05 vs positive drug group), which was not significantly different from the levels in the normal group and the positive drug group.

[0061] The above results indicate that Gomicin G hydrogel can significantly improve anxiety-like behavior in aluminum-induced AD mice, restore their central region exploration behavior to normal levels, and its overall efficacy is comparable to that of donepezil hydrochloride, a positive control drug, and superior to that of the blank hydrogel group.

[0062] 3. Y-maze experiment (1) Experimental methods The spatial recognition and memory abilities of mice in each group were evaluated using a Y-maze (three arms of equal length, with an included angle of 120°, each arm measuring 30 cm × 5 cm × 15 cm, made of matte black acrylic). The experiment consisted of two phases: a training phase and a testing phase.

[0063] Training period: Three arms were randomly assigned as the starting arm (S), other arms (O), and novel arm (N), with the novel arm closed by an opaque partition. Mice were placed at the end of the starting arm and allowed to freely explore the S and O arms for 10 minutes. The allocation of the starting and novel arms for different animals followed Latin square equilibrium.

[0064] After training, the mice were returned to their cages, and a testing period was conducted 1 hour later. The new partition in each arm was removed, and the mice were reinserted from the starting arm, allowing them to freely explore the three arms for 5 minutes. The entire process was recorded by the top camera. The time the mice spent in each arm and the number of times they entered were recorded.

[0065] (2) Experimental results Experimental results are as follows Figure 4 As shown in c, through Figure 4 As shown in c, the number of novel arm entries in the normal group mice was 4.0 ± 1. The number of novel arm entries in the aluminum-induced AD model group mice was significantly increased to 6.67 ± 1.03 (P<0.01 vs. normal group), indicating that the spatial recognition and memory ability of aluminum-induced AD mice was severely impaired, specifically manifested as a decreased ability to distinguish arms during exploration and an increased number of ineffective repeated entries. The number of novel arm entries in the positive drug control group (donepezil hydrochloride) was 4.5 ± 1.22, significantly lower than that in the model group (P<0.05 vs. model group). The number of novel arm entries in the blank hydrogel group was 5.5 ± 1.05, with no significant difference compared to the model group (P>0.05). The number of novel arm entries in the gomisin G hydrogel group was significantly reduced to 4.17 ± 0.41 (P<0.01 vs. model group; P>0.05 vs. normal group; P>0.05 vs. positive drug group), closest to the level of the normal group.

[0066] The above results indicate that Gomisin G hydrogel can significantly improve the spatial recognition and memory ability of aluminum-induced AD mice, restore their novelty exploration behavior to normal levels, and has an overall therapeutic effect superior to donepezil hydrochloride as a positive control drug.

[0067] 4. Water Maze Experiment (1) Experimental methods The Morris water maze was used to evaluate spatial learning and memory abilities in mice. Experiments were conducted on days 24 and 28 after drug administration. The water maze consisted of a circular pool (120 cm in diameter) with a hidden platform (10 cm in diameter) located 1 cm below the water surface in one quadrant. The water temperature was 22 ± 1 °C. Mice were placed into the water from different quadrants facing the pool wall, and the time it took for them to find the platform (escape latency) was recorded, with an upper limit of 180 seconds.

[0068] (2) Experimental results Results of escaping the latency period on day 28 of drug administration are as follows Figure 4 As shown in d, through Figure 4As shown in Figure d, the escape latency of mice in the normal group was 7.17 ± 1.47 s. The escape latency of mice in the aluminum-induced AD model group was significantly prolonged to 48.67 ± 5.89 s (P<0.01 vs. normal group), indicating severe impairment of spatial learning and memory in aluminum-induced AD mice. The escape latency of the positive drug control group (donepezil hydrochloride) was 20.17 ± 2.14 s, significantly shorter than the model group (P<0.05 vs. model group). The escape latency of the blank hydrogel group was 45.50 ± 5.36 s, with no significant difference compared to the model group (P>0.05). The escape latency of the gomisin G hydrogel group was significantly shortened to 12.50 ± 1.87 s (P<0.01 vs. model group; P>0.05 vs. normal group; P<0.05 vs. positive drug group), closest to the level of the normal group.

[0069] The above results indicate that Gomisin G hydrogel can significantly improve the spatial learning and memory abilities of aluminum-induced AD mice, restore their escape latency to normal levels, and is more effective than the positive control drug donepezil hydrochloride.

[0070] In summary, in the pole climbing experiment, mine experiment, Y maze experiment, and water maze experiment of Alzheimer's disease model mice, the time to reach the bottom of the pole, the time spent in the central area, the number of new arms entered, and the escape latency of aluminum-induced AD mice in the Gmisin G hydrogel group were significantly less than those in the model group and the blank hydrogel group. Moreover, the overall efficacy was better than that of donepezil hydrochloride, making it the optimal intervention program.

[0071] Example 5: Expression levels of Aβ and Tau proteins in the right hemisphere of aluminum-induced AD mice 1. Experimental Methods After the behavioral experiments, mice were euthanized and the right hemisphere of the brain was isolated. Hippocampal tissue was homogenized in RIPA lysis buffer (containing 1% PMSF protease inhibitor), centrifuged at 12,000 rpm for 15 min at 4°C, and the protein concentration of the supernatant was determined using the BCA method. Equal amounts of protein (30 μg / well) were subjected to SDS-PAGE gel electrophoresis, transferred to PVDF membranes, and blocked with 5% skim milk at room temperature for 2 h. Anti-Aβ antibody (1:1000), anti-Tau antibody (1:1000), and anti-β-Actin antibody (1:5000) were added, and the membranes were incubated overnight at 4°C. After washing, HRP-labeled secondary antibody (1:5000) was added and incubated at room temperature for 1 h. ECL chemiluminescence imaging was performed, and grayscale analysis was performed using ImageJ software.

[0072] 2. Experimental Results The results are as follows Figure 5 As shown, through Figure 5Western blotting results showed that the expression levels of Aβ and Tau proteins in the right hemisphere of the aluminum-induced AD model group were significantly increased, indicating abnormal activation of central pathological proteins. The expression levels of Aβ and Tau proteins in the gomisin G hydrogel group were significantly downregulated compared to other model groups, and there was no significant difference compared to the control group, indicating that gomisin G hydrogel can effectively inhibit the abnormal expression of core pathological proteins in AD and reverse brain damage in aluminum-induced AD mice.

[0073] Example 6: Immunofluorescent sections of the right hemisphere of aluminum-induced AD mice 1. Experimental Methods After the behavioral experiments, mice were anesthetized and fixed via cardiac perfusion with 4% paraformaldehyde. The right hemisphere was then fixed overnight in 4% paraformaldehyde at 4°C, followed by dehydration with 15% and 30% sucrose solutions until it settled. After OCT embedding, sections were frozen at -20°C (10 μm thickness). After thawing to room temperature, sections were permeabilized with 0.3% Triton X-100 for 15 min, blocked with 5% BSA for 1 h, and then incubated overnight at 4°C with anti-Aβ antibody (1:200) and anti-Tau antibody (1:200), respectively. After washing, sections were incubated with fluorescent secondary antibody (1:500) at room temperature in the dark for 1 h, stained with DAPI, mounted, and observed and images were acquired using a fluorescence microscope. Quantitative fluorescence intensity analysis was performed using ImageJ software.

[0074] 2. Experimental Results The results are as follows Figure 6 As shown, through Figure 6 Immunofluorescence staining results showed that the positive fluorescence signal intensity of Aβ protein (red fluorescence) and Tau protein (green fluorescence) in the right hemisphere of the aluminum-induced AD model group was significantly enhanced, indicating the presence of significant pathological protein deposition in the brain. The fluorescence intensity of Aβ and Tau in the gomisin G hydrogel group was significantly lower than that in other model groups, and was closest to the level in the empty saline group, indicating that gomisin G hydrogel can effectively reduce the abnormal aggregation of Aβ and Tau proteins in the brains of AD model mice.

[0075] Example 7: Levels of neutrophils in the small intestine of aluminum-induced AD mice (immunosections) 1. Experimental Methods Mouse small intestinal tissue (5 cm from the pylorus of the stomach) was collected, fixed with 4% paraformaldehyde, dehydrated with sucrose, embedded in OCT, and then frozen into sections (10 μm thick). After permeabilization and blocking, anti-CXCR2 antibody (1:200) and anti-Ly-6G antibody (1:200) were added, respectively, and incubated overnight at 4°C. After incubation with fluorescent secondary antibody (1:500) at room temperature in the dark for 1 h, the sections were stained with DAPI, mounted, observed and imaged under a fluorescence microscope, and the fluorescence intensity was quantitatively analyzed using ImageJ software.

[0076] 2. Experimental Results The results are as follows Figure 7 As shown, through Figure 7 Immunofluorescence staining results showed that the fluorescence signals of CXCR2 and LY-6G in the small intestine of aluminum-induced AD model mice were significantly increased. After treatment with gomisin G hydrogel and donepezil hydrochloride, the fluorescence intensity of both was significantly reduced, indicating that neutrophil infiltration was inhibited and the intestinal inflammatory microenvironment was improved.

[0077] Example 8 Release performance 1. Experimental Methods The in vitro release behavior of gomisin G hydrogel was investigated using dynamic dialysis. Approximately 2 mg of gomisin G hydrogel prepared in Example 1 (containing gomisin G) was accurately weighed and placed in a pretreated dialysis bag (molecular weight cutoff 8000–14000 Da). The bag was sealed at both ends and placed in a beaker containing 100 mL of release medium (pH 7.4 phosphate buffer, containing 0.5% Tween-80 to maintain leak conditions). The mixture was stirred at 100 r / min in a constant temperature water bath at 37 ± 0.5 °C. A control group was also included: an equal volume of gomisin G active pharmaceutical ingredient was directly dissolved in a release medium containing an equal volume of solubilizer and dialyzed using the same method.

[0078] At preset time points (0.5, 1, 6, 12, 24, and 72 h), 2 mL of release medium was collected, and an equal volume of fresh medium was added at the same temperature. After filtration through a 0.22 μm microporous membrane, the content of gemicin G was determined by high-performance liquid chromatography (HPLC), and the cumulative release rate was calculated. Each experiment was performed in parallel six times, and the results are expressed as mean ± standard deviation (Mean ± SD).

[0079] 2. Experimental Results The in vitro cumulative release curve of Gomicin G hydrogel is shown in Figure 1. Figure 8 As shown in the figure. The results showed that the cumulative release rate of the gomisin G active pharmaceutical ingredient solution reached 91.6 ± 3.3% within 12 h, indicating rapid and almost complete release. In contrast, the gomisin G hydrogel exhibited obvious sustained-release characteristics: a rapid release phase occurred from 0 to 6 h, with a cumulative release rate of 35.6 ± 3.1%, possibly related to the rapid diffusion of the weakly adsorbed drug on the surface and near the surface of the hydrogel; a slow release phase occurred from 6 to 24 h, with the cumulative release rate increasing from 35.6% to 56.8 ± 3.6%; and a plateau phase occurred from 24 to 72 h, with a cumulative release rate of 78.5 ± 3.8% at 72 h. The cumulative release rate data at each time point are shown in the figure. Figure 8 .

[0080] 3. Experimental Conclusions The above results demonstrate that the gomisin G hydrogel prepared in this invention can achieve sustained and slow release of gomisin G, effectively prolonging the duration of drug action. Compared with the gomisin G active pharmaceutical ingredient solution, which is essentially completely released within 12 hours, the gomisin G hydrogel maintains sustained release for 72 hours, significantly improving the problems of burst release and low local bioavailability of gomisin G due to its poor water solubility. This sustained-release characteristic is beneficial for maintaining an effective drug concentration of gomisin G in the intestinal inflammatory lesion area and prolonging the duration of drug effect, providing a good formulation basis for its oral treatment of Alzheimer's disease.

[0081] Example 9 Toxicity test of Gomicin G hydrogel 1. Experimental Objective To evaluate the safety of Gomicin G and drug-loaded nanoparticle hydrogels in mice; to investigate their systemic toxicity, local irritation, and effects on organs and nervous tissues, providing a safety basis for future applications.

[0082] 2. Experimental equipment Gomisin G, nanoparticle hydrogels, electronic balances, and SPF-grade Kunming mice (half male, half female, weighing 18-22 g) were used. They were housed in an environment with a temperature of 22±2℃, humidity of 50±10%, and a 12-hour light-dark cycle, with free access to food and water. Experiments began after 3 days of acclimatization. This experiment was reviewed and approved by the Laboratory Animal Ethics Committee and complied with laboratory animal welfare and ethical guidelines throughout.

[0083] 3. Experimental Procedure Six healthy male SPF-grade black mice (to avoid interference from fluctuations in estrogen levels), 8 weeks old, weighing 20-25g, were administered the mice by gavage for 7 consecutive days, serving as a control group with six normally fed mice. During the experiment, the mice's behavior, mental state, and injection site reactions were observed daily, and they were weighed daily.

[0084] 4. Experimental Results During the experiment, no mice in any group died, showed no signs of poisoning or local irritation, and their weight increased steadily.

[0085] 5. Results Analysis At the experimental dosage, Gomicin G and drug-loaded nanoparticle hydrogels did not cause death, toxicity, or local irritation in mice. The weight gain of mice in each group was stable and not significantly different from the normal control group, as shown in Table 1. This indicates that the drug and its formulation have no significant systemic toxicity, good biocompatibility, and no significant organ or tissue damage in mice, demonstrating high safety and meeting the safety requirements for long-term drug administration in subsequent animal experiments, thus proving its feasibility.

[0086] Table 1

[0087] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A Gomisin G hydrogel based on lyophilization remodeling method, characterized in that, The gomisin G hydrogel comprises gomisin G, a solubilizer, a polymer material, a coagulant, and a lyophilization protectant.

2. Gomisin G hydrogel based on lyophilized remodeling method according to claim 1, characterized in that, The mass ratio of the gomisin G, solubilizer, polymer material, coagulant and freeze-drying protectant is 1: (5-100): (100-1000): (1-10): (10-100).

3. Gomisin G hydrogel based on lyophilization remodeling method according to claim 2, characterized in that, The particle size of the Gomisin G is 100-120 nm; The solubilizer includes one or more of polyethylene glycol derivatives, polysialic acid derivatives, polylactic acid derivatives, and phospholipids.

4. Gomisin G hydrogel based on lyophilized remodeling method according to claim 2, characterized in that, The polymeric material includes one or more of chitosan, polyhyaluronic acid, sodium carboxymethyl cellulose, and polysialic acid.

5. The gomisin G hydrogel based on freeze-drying remodeling method according to claim 2, characterized in that, The coagulant includes one or more of calcium chloride, zinc chloride, aluminum chloride, and magnesium chloride.

6. The gomisin G hydrogel based on freeze-drying remodeling method according to claim 2, characterized in that, The freeze-drying protectant includes one or more of sucrose, maltose, glucose, and lactose.

7. A method for preparing gomisin G hydrogel based on freeze-drying remodeling as described in any one of claims 1-6, characterized in that, Includes the following steps: (1) Gomexin G and solubilizer are mixed and dissolved in anhydrous ethanol to obtain an organic phase. The organic phase is then mixed with an aqueous phase to obtain a Gomexin G solution. (2) Add a coagulant to the polymer material, and obtain a blank hydrogel after cross-linking reaction. Then add a freeze-drying protectant to wash the blank hydrogel, then freeze-dry it, and finally add the gomisin G solution to re-dissolve it to obtain the gomisin G hydrogel.

8. The preparation method according to claim 7, characterized in that, The mixing ratio of gomisin G and anhydrous ethanol in step (1) is 1 mg: (10-100) mL; The volume ratio of the organic phase to the aqueous phase is 1:(10-20).

9. The preparation method according to claim 7, characterized in that, The freeze-drying process in step (2) is carried out at a temperature of -40°C for 24 hours.

10. The use of the gomisin G hydrogel based on the freeze-drying remodeling method as described in any one of claims 1-6 in the preparation of a medicament for treating Alzheimer's disease.